Analisis Kendala Jobdesc Admin Administrasi Sales Rental Dan Penjualan Unit Di PT Bina Pertiwi Menggunakan Fishbone Diagram - Giga Dewi Septiana; Akmal Suryadi (International Forum of Researchers and Lecturers, 2024)
The faster economic development in the world causes tighter business competition. Plus the rapid progress of increasingly sophisticated technology. Many companies are currently competing to use technology to increase performance efficiency advantages in other companies and competition. Information technology that is quite popular in the current generation is System Application and Product In Data Processing (SAP). SAP is a system that runs a business using one database which can then be accessed by all departments in the company. This research aims to provide evaluation and input on the problems faced by SAP admin sales users at PT Bina Pertiwi Surabaya Branch. In this research, a qualitative approach was used by conducting interviews with resource persons from the administration department and Branch Administration Supervisors using a fishbone diagram. The results of the evaluation of the implementation of the admin job description for sales rental administration and units using SAP are quite good, but there are still problems caused by discrepancies between the actual cash in and the cash in plan, so AR monitoring must be carried out.